Analisis Perhitungan Quantity Take Off Jembatan Rangka Baja Menggunakan Metode (BIM) dengan Autodesk Revit(Studi Kasus: Perencanaan Jembatan Ruas Selat Baru - Deluk) - Azmi Maulana; Dedi Enda (Jurnal Ragam Pengabdian, 2026)
The construction industry is increasingly adopting Building Information Modeling (BIM) to support Quantity Take Off (QTO), as conventional methods based on two-dimensional drawings, which are still widely used in Indonesia, are prone to measurement errors, inconsistent results, and time inefficiency. This study aimed to develop a three-dimensional BIM model of a steel truss bridge using a case study of the Selat Baru–Deluk Bridge with Autodesk Revit and compare the calculated concrete and reinforcement volumes with manual calculations. The model was developed by converting two-dimensional Detail Engineering Design (DED) drawings into a three-dimensional model. Volume calculations were automatically generated using the Schedule/Quantities feature in Autodesk Revit, while the conventional method used simple geometric formulas. The results showed that the average difference between the two methods was only 0.107% for concrete and 0.463% for reinforcement. The Root Mean Square Error (RMSE) values were 0.511% for concrete and 1.402% for reinforcement. These findings indicate that BIM-based quantity estimation using Autodesk Revit provides higher accuracy, efficiency, and precision compared to conventional methods in bridge QTO calculations.